Sosialisasi Kewirausahaan Guna Memotivasi Siwa Siswi Untuk Berwirausaha Serta Mempelajari Kegiatan Administrasi - Alfiatus Zainiyah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The Surabaya Mengajar Program is designed to improve students reading, writing and arimathic skills. This program prepare students to face future challenges and become effective leaders. This program involes student from various universities in Surabaya. Before the program start, students and supervisors coordinate/brief. They visit, namely to take part in the Surabaya Mengajar Program. After observations on September 4 2023, the Surabaya Mengajar Program activities were immediately carried out te next day, namely on September 5 2023. One of the benefits of participacing in this program is that student get the opportunity to communicate and interact with many people, as well as knowing the latest learning and teaching systems in the Merdeka Curriculum. Student also gain insight into office administration at SDN Kendangsari IV/279 Surabaya. The Surabaya Mengajar 4 program aims to improve student literacy and numeracy in schools. This program also provide many benefit for student who take part in this program. Students get the opportunity to learn and develop their skills in their skills in their field. Students also have to the oppurtinity to collaborate with teachers at schools and improve the quality of education at school.